Penentuan Enterprise Value Berdasarkan Keputusan Perusahaan, Laba, dan Aktivitas Operasi - Febriyanti, Bella; Indah, Nopiani (Journal of Business and Economics Research (JBE), 2025)
This study aims to analyze the effect of investment decisions, financing decisions, earnings persistence, earnings quality, and operating activities on firm value in the energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The data used in this research are secondary data obtained from the financial statements of each listed company, with a population of 56 companies and a total sample of 280 observations. The statistical analysis was conducted using EViews 13 software. Data analysis included model selection tests, multicollinearity tests, heteroscedasticity tests, coefficient of determination (R²), t-tests, and F-tests. The findings of this study indicate that (1) Investment decisions have no significant effect on firm value as shown by the regression coefficient t-statistic for variable X1 of -1.85, which is less than the t-table value of 1.96, with a significance level (p-value) of 0.06 > 0.05, (2) Financing decisions have no significant effect on firm value as indicated by the t-statistic for variable X2 of -0.18 < 1.96, with a p-value of 0.87 > 0.05, (3) Earnings quality has no significant effect on firm value as the t-statistic for variable X3 is 0.82 < 1.96, with a p-value of 0.41 > 0.05, (4) Earnings persistence has a significant effect on firm value as evidenced by the t-statistic for variable X4 of 5.12 > 1.96, and p-value of 0.00 < 0.05, and (5) Operating activities have no significant effect on firm value, as indicated by the t-statistic for variable X5 of -0.74 < 1.96, with a p-value of 0.46 > 0.05.